2020
DOI: 10.1002/ijgo.13259
|View full text |Cite
|
Sign up to set email alerts
|

Miscarriage, stillbirth, and infant death in an oil‐polluted region of the Niger Delta, Nigeria: A retrospective cohort study

Abstract: Objective: To determine the association between oil pollution and miscarriage, stillbirth, and infant death in the Niger Delta region of Nigeria. Methods: A retrospective cohort study was undertaken of pregnant women (aged 18-45 years) who attended selected health facilities in regions with high and low exposure to oil pollution from May 14, 2018, to September 27, 2018. A multistage sampling technique was used to randomly select a representative of women with high and low exposure to oil pollution. An intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The Niger Delta region of Nigeria is currently home to at least 123 gas flaring sites, which has made Nigeria one of the top greenhouse gas emitters in Africa (Bodo and Gimah 2020;Oghenetega et al 2022). According to Oghenetega et al (2020), there is evidence to suggest that both oil spills and gas flaring have a negative impact on the health outcomes of mothers and newborns. Exposure to gas flaring over a prolonged period, such as in the Niger Delta region of Nigeria, can lead to a rise in health anomalies among local residents, according to Adinkwu et al (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The Niger Delta region of Nigeria is currently home to at least 123 gas flaring sites, which has made Nigeria one of the top greenhouse gas emitters in Africa (Bodo and Gimah 2020;Oghenetega et al 2022). According to Oghenetega et al (2020), there is evidence to suggest that both oil spills and gas flaring have a negative impact on the health outcomes of mothers and newborns. Exposure to gas flaring over a prolonged period, such as in the Niger Delta region of Nigeria, can lead to a rise in health anomalies among local residents, according to Adinkwu et al (2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The authors have further pointed out that these oil spills pose significant health risks to human beings, including the development of derma-toxic diseases, cancer, and high rates of neonatal and child mortality. A study conducted by Oghenetega et al (2020) established a correlation between oil pollution in Nigeria's Niger Delta region and higher rates of miscarriage, stillbirth, and infant mortality. The long-term effects of oil pollution on marine ecosystems and their resilience remain a critical area of concern for researchers and policymakers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Environmental pollutants such as volatile organic compounds (VOCs), heavy metals, polycyclic aromatic hydrocarbons (PAHs) are released when oil is spilt, and gas flared [1]. Several authors have reported that living in areas polluted by oil have adverse effects on human health [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The authors have further pointed out that these oil spills pose signi cant health risks to human beings, including the development of derma-toxic diseases, cancer, and high rates of neonatal and child mortality. A study conducted byOghenetega et al (2020b) established a correlation between oil pollution in Nigeria's Niger Delta region and higher rates of miscarriage, stillbirth, and infant mortality. The…”
mentioning
confidence: 99%